PENYUSUNAN INDEKS PSIKOMETRIK KEWIRAUSAHAAN PERBANDINGAN MAHASISWA INDONESIA DAN MALAYSIA - Murni, Isteti binti; noviarti, noviarti binti (LLDIKTI Wilayah X, 2014)
This research aims to analyze an instrument to measure the entrepreneurship index to compare between the two countries among the students have entrepreneurial potential. Based on Entrepreneurship index (NorAishah 2007) version of the instrument was translated into Indonesian language. These same instrument with two different languages was tested in both countries to determine if the itemsâreliability will have almost similar scores. The number of samples for both countries were more than 262 students. The results showed that the total Cronbach Alpha values were almost the same for both countries after dropping some items with less than 0.5 Cronbach Alpha values. For example, the Cronbach Alpha values for the Malaysian version were the attitude (0.882), entrepreneurial thinking (0.962) and entrepreneurial behavior (0.785).Â The Cronbach Alpha values for the Indonesion version were the attitude (0.785), entrepreneurial thinking (0.620) and entrepreneurial behavior (0.910).Â In comparison, the Malaysian version scored a little bit higher than her counterpart in Indonesia. However, on administering the instrument in its own language in the two countries on their undergraduates found that the Indonesian students scored higher for all of the three components. This result could explain for the cultural reasons of the higher scores in terms of Indonesian studentsâ attitude, thinking and behavior than the Malaysian students. Â